RANKING THE BUILDINGS OVER A DEVELOPED LARGE GEOGRAPHIC AREA ACCORDING TO THEIR EXPOSURE TO THE LANDSLIDE HAZARD - DI FELICE, Paolino; BUFALINO, Andrea; CAROCCI, Eugenio; DI GIUSEPPE, Lorenzo; GENTILE, Matteo; RANALLI, Alessandro; SALINI, Andrea (European Journal of Geography, 2023)
In this paper, we focus on public buildings. They represent a relevant category of elements because of their intrinsic economic value and because their damage may cause human casualties as well. If the survey covers developed, large geographic areas, the number of buildings potentially at risk exposed is very high. Such numbers make the use of the available methods of building risk assessment highly time-consuming and, hence, inapplicable in the reality. To mitigate such an issue, we introduce a method that takes as input all the buildings standing over the study area and outputs a ranking about them according to their degree of exposure to the landslide hazard. The practitioners in mitigation can extract from the ranking the top-N buildings to look at. Then, they need to carry out the detailed risk assessment only for the buildings on the short list. This way the overall processing time required for the computation of the vulnerability, and hence of the risk, is reduced dramatically. The ranking method has been tested to assess the exposure to the landslide hazard of the buildings hosting public schools in the Abruzzo Region (center of Italy), a large area (11,000 km2) with 1,330,000 inhabitants. The results obtained from the case study show that the top-N buildings to look at are a very small fraction of the total number of buildings in the region.